Operations Without Pain: The Practice and Science of Anaesthesia in Victorian Britain - Snow, S. author. aut Link
XII, 271 p.
Keywords: The introduction of anaesthesia to Victorian Britain marked a defining moment between modern medicine and earlier practices. This book uses new information from John Snow's casebooks and London hospital archives to revise many of the existing historical assumptions about the early history of surgical anaesthesia. By examining complex patterns of innovation, reversals, debate and geographical difference, Stephanie Snow shows how anaesthesia became established as a routine part of British medicine.